Seasonal Data on Flying and Airborne Invertebrates Collected by Suction Trap near Jandakot, Western Australia - Taylor, J. (1980)
Numbers of individual flying insects and airborne invertebrates in each of 56 broad taxonomic groups,captured weekly in 1972 in a suction trap,are tabulated to show frequency distributions through the year. Additional data are given on species and genera when known.